mhealth-based interventions to improving liver cancer screening among high-risk populations: a study protocol for a randomized controlled trial - Ge-hui Feng; Ke-hao Zhao; Yi-fei Wang; Qian-qian Yue; Yun-shan Chen; Li-li Huang; Xin-ru Meng; Tong Peng; Ying Zeng (BMC, 2024)
Abstract Background Liver cancer (LC) screening, such as AFP test and abdominal ultrasound, is an effective way to prevent LC, one of the most common cancers worldwide. Despite the proven screening benefits, screening participation among high-risk populations for LC remains low. This suggests that targeted, systematic, and effective interventions should be provided to improve knowledge and awareness related to LC screening, enhance screening intentions, and thereby promote screening behaviors. Telephone is people's main medium of daily communication and mHealth-based programs offer a potential and effective solution for promoting health behaviors. The purpose of this study is to develop and implement a mHealth (WeChat app) based intervention guided by Fogg's Behavior Model (FBM) to augment the knowledge of LC prevention among people at risk of LC and enhance their motivation for screening, and to validate its effectiveness in improving LC screening. Methods We propose a two-arm, single-blind randomized controlled trial with 82 at-risk individuals of LC, delivering a 6-month mHealth-based intervention program with optional health counseling. Recruitment will be through tertiary hospitals and community organizations in 4 districts in Heng Yang. In total, 82 individuals at high risk for HCC will be randomized 1:1 to intervention or control (usual care) groups. The intervention group will receive intervention, whose contents are based on the FBM model, via multiple forms of media including PowerPoint presentation, multimedia video, health information booklet and screening message, which is delivered in the WeChat Applet. Control dyads will be provided with usual health education. Outcomes will be assessed at baseline and post-intervention. Discussion The findings of this study will provide evidence of the benefits of utilizing mHealth-based approaches in intervention development to enhance the effectiveness of screening adherence for high-risk people of LC. Further, the findings would provide reference to the potential incorporation of the targeted intervention in local community organizations. Trial registration Chinese Clinical Trial Registry (ChiCTR2400080530) Date registered: 31/1/2024.